Assessing morbidity in the paediatric community - Escuder Maria Mercedes L; Silva Nilza N da; Pereira Júlio CR; Puccini Rosana F; Herrman Anneliese A (Universidade de São Paulo, 1999)
INTRODUCTION: Morbidity information is easily available from medical records but its scope is limited to the population attended by the health services. Information on the prevalence of diseases requires community surveys, which are not always feasible. These two sources of information represent two alternative assessments of disease occurrence, namely demand morbidity and perceived morbidity. The present study was conceived so as to elicit a potential relationship between them so that the former could be used in the absence of the latter. METHODS: A community of 13,365 families on the outskirts of S. Paulo, Brazil, was studied during the period from 15/Nov/1994 to 15/Jan/1995. Data regarding children less than 5 years old were collected from a household survey and from the 2 basic health units in the area. Prevalence of diseases was ascertained from perceived morbidity and compared to estimates computed from demand morbidity. RESULTS: Data analysis distinguished 2 age groups, infants less than 1 year old and children 1 to less than 5. The most important groups of diseases were respiratory diseases, diarrhoea, skin problems and infectious & parasitical diseases. Basic health units presented a better coverage for infants. Though disease frequencies were not different within or outside these units, a better coverage was found for diarrhoea and infectious & parasitical diseases in the infant group, and for diarrhoea in the older age group. Equivalence between the two types of morbidity was found to be limited to the infant group and concerned only the best covered diseases. The odds of a disease being seen at the health service should be of at least 4:10 to ensure this equivalence. CONCLUSION: It was concluded that, provided that health service coverage is good, demand morbidity can be taken as a reliable estimate of community morbidity.